Is atmospheric phosphorus pollution altering global alpine Lake stoichiometry?. Issue 9 (9th September 2015) - Brahney, Janice; Mahowald, Natalie; Ward, Daniel S.; Ballantyne, Ashley P.; Neff, Jason C.
Abstract Anthropogenic activities have significantly altered atmospheric chemistry and changed the global mobility of key macronutrients. Here we show that contemporary global patterns in nitrogen (N) and phosphorus (P) emissions drive large hemispheric variation in precipitation chemistry. These global patterns of nutrient emission and deposition (N:P) are in turn closely reflected in the water chemistry of naturally oligotrophic lakes (r2 = 0.81, p < 0.0001). Observed increases in anthropogenic N deposition play a role in nutrient concentrations (r2 = 0.20, p < 0.05); however, atmospheric deposition of P appears to be major contributor to this pattern (r2 = 0.65, p < 0.0001). Atmospheric simulations indicate a global increase in P deposition by 1.4 times the preindustrial rate largely due to increased dust and biomass burning emissions. Although changes in the mass flux of global P deposition are smaller than for N, the impacts on primary productivity may be greater because, on average, one unit of increased P deposition has 16 times the influence of one unit of N deposition. These stoichiometric considerations, combined with the evidence presented here, suggest that increases in P deposition may be a major driver of alpine Lake trophic status, particularly in the Southern Hemisphere. These results underscore the need for the broader scientific community to consider the impact of atmospheric phosphorus deposition on the water quality of naturally oligotrophic lakes.